1998
DOI: 10.1116/1.581530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma conditions on the shapes of features etched in Cl2 and HBr plasmas. I. Bulk crystalline silicon etching

Abstract: We have studied the effects of source and bias powers, pressure, and feed gas composition on the shapes of SiO2-masked crystalline silicon features etched in a transformer-coupled high density plasma system. Higher etching rates were obtained at higher source and bias powers, and higher pressure. The etching rates of isolated and nested trenches, isolated lines, and holes were nearly the same, indicating a negligible pattern density dependence. We did, however, observe a very weak decrease in etch rates with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[32][33][34][35][36][37][38] Undercutting in HBr-containing plasmas is usually not observed. [39][40][41][42][43][44] Perhaps this is a result of the erosion of photoresist and chamber materials (with no Faraday shield, as in most commercial etching tools), resulting in passivating layers on the Si sidewalls 42 that could slow or block isotropic etching by H atoms. Haverlag et al 42 reported undercutting of poly-Si beneath a photoresist mask exposed in an electron cyclotron resonance 5 mTorr HBr plasma at a modest substrate temperature (48 C) and low rf bias voltage (50 V).…”
Section: Isotropic Chemical Etchingmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] Undercutting in HBr-containing plasmas is usually not observed. [39][40][41][42][43][44] Perhaps this is a result of the erosion of photoresist and chamber materials (with no Faraday shield, as in most commercial etching tools), resulting in passivating layers on the Si sidewalls 42 that could slow or block isotropic etching by H atoms. Haverlag et al 42 reported undercutting of poly-Si beneath a photoresist mask exposed in an electron cyclotron resonance 5 mTorr HBr plasma at a modest substrate temperature (48 C) and low rf bias voltage (50 V).…”
Section: Isotropic Chemical Etchingmentioning
confidence: 99%
“…5 Experimental studies and modeling of profile development in sub-micron patterned Si undergoing Cl 2 and HBr dry etching have evolved over the last 10 years. 5,[7][8][9][10][11][12][13][14][15] For the purpose of precisely controlling profiles for imprint templates for nanodevices, we extended the experimental studies to the nanoscale regime. 16,17 Here we discuss how ion interactions with the feature sidewalls and mask can completely dominate the overall feature shape as features shrink.…”
Section: Introductionmentioning
confidence: 99%
“…Vyvoda et al studied the effects of source and bias powers, pressure, and feed gas composition on the feature profiles of SiO 2 -masked crystalline silicon etched in Cl 2 /HBr transformer-coupled plasmas (TCP). 3) They obtained higher etch rates at higher source powers, bias powers, and pressures. When HBr was used instead of Cl 2 , etch rate decreased substantially, but the etch profile became more vertical and the trench bottom became flatter.…”
Section: Introductionmentioning
confidence: 99%